PEMBANGUNAN BERKELANJUTAN DALAM REKONSTRUKSI RUMAH PASCA GEMPA YOGYAKARTA 2006 DI DUSUN NGIBIKAN, BANTUL - Setyonugroho, Gregorius Agung (Universitas Atma Jaya Yogyakarta, 2013)
Abstract: Ngibikan Village is located approximately 10 kilometers from the Yogyakarta 2006 earthquakeâ€™s epicenter. Through design development by Eko Prawoto Ì¶ a professional architect who has a concern in humanitarian relief Ì¶ compromised by beneficiaries agreements and also â€œKompasâ€ Humanitarian Funds as the funding donor, they started the Ngibikan Village houses reconstruction one week after earthquake and finished only in four months. Flexibility design in structure module configuration and layout allowed community to decide their needs with their own initiatives. Ngibikan Village reconstruction brought a new experience in reconstructing a timber structure house by their community. This new â€˜knowledgeâ€™ contributed to the sustainability development of their houses. There are many housesâ€™ improvements that visible in five years post-reconstruction at this village. These improvements are in the transformation of their existed core housesâ€™ structure module configurations, extension or additional buildings that added, and other additional developments. All these improvements were built in order to accommodate their additional needs since the priority need of a core house as their permanent shelter has been completed. Nowadays, houses physical condition and its various transformations are still in a progress of sustainability development for present time and in the future.Keywords: reconstruction, transformation, design development, core houseAbstrak: Dusun Ngibikan berlokasi kurang lebih 10 kilometer dari pusat gempa besar yang pernah terjadi di Yogyakarta pada tahun 2006 yang lalu. Melalui pengembangan desain yang dilakukan oleh Eko Prawoto Ì¶ seorang arsitek profesional yang peduli dalam hal kemanusiaanÌ¶Â Â bersama-sama dengan para korban gempa penerima bantuan serta melalui donasi dari Dana Kemanusiaan Kompas, dimulailah proses rekonstruksi rumah warga Dusun Ngibikan yang dimulai seminggu setelah terjadinya gempa bumi hingga selesai dalam kurun waktu empat bulan. Fleksibilitas desain pada konfigurasi modul struktur dan pengaturan â€œlayoutâ€ keruangan memberikan kesempatan bagi para penduduk untuk berinisiatif mengembangkan desain â€œlayoutâ€ serta tampak rumah mereka masing-masing. Proses rekonstruksi rumah warga Dusun Ngibikan telah memberikan pengalaman baru bagi para warganya dalam hal membangun rumah dengan menggunakan struktur kayu sebagai material rangka utamanya. Pengalaman baru ini telah memberikan kontribusi yang positif dalam konsep pengembangan rumah yang berkelanjutan. Dalam kurun waktu lima tahun pasca rekonstruksi, dapat dijumpai beberapa kondisi rumah yang telah berkembang dari kondisi morfologi awalnya. Transformasi yang terjadi pada dasarnya ditujukan dalam rangka pemenuhan kebutuhan-kebutuhan utama dari anggota penghuni rumah warga Dusun Ngibikan tersebut. Kondisi saat ini pun masih merupakan suatu proses pengembangan berkelanjutan yang memungkinkan adanya transformasi-transformasi lain pada masa yang akan datang.Kata kunci: rekonstruksi, transformasi, pengembangan desain, core houseÂ